Public Opinion and National Security in Western Europe - Eichenberg, Richard C. author. aut Link
XVI, 293 p.
Keywords: This survey of European public opinion on national security issues interprets numerous public opinion polls retrieved from government ministries, commercial agencies and educational institutions. It is a comparative and historical survey of the security challenges faced by Western governments.